The Role of Artificial Intelligence for Value Creation in Digital Commerce - Abduljabbar, Sardar; Shaban, Rabeen S. (AI Society & STMIK Indonesia, 2024)
In the world of digital commerce, Artificial intelligence (AI) is starting to shift the game and transform how organizations run. AI benefits firms and consumers both in retail and digital commerce. This review provides a comprehensive analysis of the critical role AI plays in fostering value creation in the digital commerce industry, with a particular emphasis on the ways in which task and information complexity affect the application of AI technologies. The review then looks at AI possibilities in digital commerce from a variety of angles, such as supply chain efficiency, cost savings, product recommendation, enhanced customer experience and marketing plans. The aim of this review is to exploring how AI applications create value in e-commerce. The approach that was employed described the search technique for locating pertinent academic sources and was based on a survey of the literature on recent 15 studies about the effect of AI for Value Creation in Digital Commerce. Finally, the findings demonstrate that utilizing AI as an advanced instrument in the digital commerce sector appears to be a positive move since it applying AI may foster creativity, improve decision-making, and enhance overall marketing performance.